2006
DOI: 10.1089/cap.2006.16.755
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Rivastigmine in Adolescents with Down Syndrome: A Preliminary 20-Week, Open-Label Study

Abstract: Individuals with Down syndrome (DS) exhibit a cholinergic deficiency similar to that found in Alzheimer's disease. Cholinesterase inhibitors, used to treat Alzheimer's disease, may improve cognitive function in individuals with DS. This is the first investigation of the safety and efficacy of rivastigmine (an acetyl and butyryl cholinesterase inhibitor) on specific cognitive domains in pediatric DS. Eleven subjects with DS (ages 10-17 years) were treated with a liquid formulation of rivastigmine. Four subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 15 publications
1
39
0
1
Order By: Relevance
“…The Corsi Block Tapping Forward (sum of the number of digits in trials remembered correctly) measures visuospatial memory (Shapiro et al, 1992). The NEPSY Visual Attention subtest assesses visual attention (Visual Attention Accuracy) and processing speed (Visual Attention Time) and is appropriate in DS (Heller et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…The Corsi Block Tapping Forward (sum of the number of digits in trials remembered correctly) measures visuospatial memory (Shapiro et al, 1992). The NEPSY Visual Attention subtest assesses visual attention (Visual Attention Accuracy) and processing speed (Visual Attention Time) and is appropriate in DS (Heller et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…The VABS‐II is a commonly used measure of adaptive behavior in individuals with ID. It has also been included as an efficacy measure in a number of clinical trials including individuals with DS (Heller et al, ; Kishnani et al, ; Spiridigliozzi et al, ). The VABS‐II Survey Interview Form was used in the present study to measure participants' level of adaptive behavior, as reported by their parent or primary caregiver.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease, Down's syndrome, Parkinson's disease, and schizophrenia are generally characterized by progressive diminution in cognitive function associated with the loss of cholinergic neurons and synapses in the brain 15. For example, in Alzheimer's disease, the severity of cognitive dysfunction is correlated with loss of cholinergic synaptic elements in the cortex and subcortical brain areas 612.…”
Section: Introductionmentioning
confidence: 99%